(untitled) (Research, Society and Development, 2022)
With a historical and social hermeneutics, through the interdisciplinarity provided in this work by the link between history, sociology and literature, this article analyzes the thematic relationship between torture and the tortured body, based on the testimonial literature, specifically the testimonial content. in the short story O Leite em Pó da Bondade Humana (1983) by Haroldo Maranhão. In this bias, the objective of the work is to explore the violence in front of the tortured body in the aforementioned work. Thus, the literary manifestation in this narrative, in the contemporary context of Brazilian, Amazonian and Pará literature, allows us to perceive that the work studied is part of the narrative collections of testimonial literature, specifically of testimonial content, which are established from the XX th century, concomitant political oppression is known, as well as exposing the atrocities that political prisoners suffered during the 1964 military dictatorship in Brazil, in which it reveals a real scenario experienced by people who resisted the repressions of that time.